L’engagement du corps : un enjeu dans le pilotage en ligne d’un avion à cockpit de verre (glass-cockpit) - Caroline Moricot (Perspectives Interdisciplinaires sur le Travail et la Santé, 2000)
When a new generation of aircraft (glass-cockpits) came into service in the early nineties, a violent controversy ensued. One of the main issues of the dispute concerning the glass cockpits related to the problem of physical sensations, and in particular the fact that the pilots felt they were deprived of sensory information feedback. With regard to the ways in which the pilots use their bodies and their physical sensations, it became very clear that a certain amount of tension existed between automation, which tends to keep the body at a distance, and appropriation, in which the body is one of the main factors. This paper is based on the pilots’ experiences, and gives an account of how the immediacy or distance of the body helps define humans and their role in an automated environment.